Effect of conceptual change text approach on removal of students' misconceptions about heat and temperature. (1st January 2012) - Turgut, Umit; Gurbuz, Fatih
This study focuses on students' misconceptions regarding heat and temperature, the effectiveness of conceptual change text instruction on students' understanding of heat and temperature and their attitudes towards science. Conceptual change and traditional instruction methods were used as teaching methods in the study. The results showed that the students have misconceptions and the experimental group students performed better with respect to the success in eliminating the misconception compared to the control group. In addition, it has been found that there was no significant difference between the attitudes of students in the experimental and control groups both before and after teaching. Teaching strategies can be used to determine the misconceptions and enhance students' understanding. Moreover, results showed that there were no statistically significant differences of post-test and delayed test.